2019
DOI: 10.1097/md.0000000000015202
|View full text |Cite
|
Sign up to set email alerts
|

Role of tranexamic acid in nasal surgery

Abstract: Objective: Nasal surgeries (such as Functional Endoscopic Sinus Surgery, Rhinoplasty, and Septorhinoplasty) are popular procedures. But perioperative bleeding, eyelid edema, and periorbital ecchymosis remain problems. Tranexamic acid (TXA) is an antifibrinolytic, and it was used to reduce the perioperative bleeding. However, there is no enough evidence judging its safety and efficiency. Therefore, a meta-analysis is conducted by us to evaluate the role of TXA in patients undergoing nasal surgeries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 33 publications
(44 reference statements)
1
22
0
Order By: Relevance
“…Randomized controlled trials on the use of tranexamic acid in rhinoplasty generally address systemic administration. 20,22…”
Section: Cocktail Solutions: Adding Tranexamic Acid To Local Anesthet...mentioning
confidence: 99%
See 2 more Smart Citations
“…Randomized controlled trials on the use of tranexamic acid in rhinoplasty generally address systemic administration. 20,22…”
Section: Cocktail Solutions: Adding Tranexamic Acid To Local Anesthet...mentioning
confidence: 99%
“…Randomized controlled trials on the use of tranexamic acid in rhinoplasty generally address systemic administration. 20,22 In the four randomized controlled trials by our group and Zilinsky's group 31,58,60,61 (Tables 1 and 2), the effect of tranexamic acid alone as a hemostatic was examined, although both groups normally use cocktails with both lidocaine and adrenaline. More research is needed on a possible synergy between adrenaline and tranexamic acid for hemostasis in soft tissue.…”
Section: Cocktail Solutions: Adding Tranexamic Acid To Local Anesthet...mentioning
confidence: 99%
See 1 more Smart Citation
“…7,16,17 A separate meta-analysis of 11 RCTs came to these same conclusions. 16 Placebo-controlled trials specifically examining iv TXA given at induction of anesthesia have demonstrated a significant reduction in intraoperative bleeding and improved surgical visualization, although one recent RCT did not demonstrate any such benefit. [18][19][20][21] A Cochrane review in 2017 proposed postoperative bleeding as a target outcome, but no designed studies since that time had been identified to answer the question.…”
Section: Discussionmentioning
confidence: 60%
“…Bleeding in EES is a major concern for the operating surgeon because the non-dominant hand also must hold the endoscope. Techniques utilized to achieve hemostasis include diathermy probes (monopolar and bipolar) [11], diluted epinephrine injection, epinephrine-soaked cotton balls that can also be used as adjuncts for soft tissue dissection [18], and preoperative injection of tranexamic acid [12] which is an anti-fibrinolytic used in a variety of surgical procedures [19][20][21].…”
Section: Discussionmentioning
confidence: 99%